2012
DOI: 10.1071/rdv24n1ab161
|View full text |Cite
|
Sign up to set email alerts
|

161 in Vitro Fertilization of Dromedary Camel (Camelus Dromedarius) Oocytes With Epididymal Spermatozoa

Abstract: Various techniques such as AI and ET have been reported to improve reproductive efficiency and genetic potential in camelids. In vitro fertilization and the development of IVP embryos are considered an alternative for genetic improvement in this species. This study investigated the effects of different sperm cell concentrations (1, 2, 3 and 4 × 106 sperm mL–1), different capacitating materials (5 mM caffeine, 10 μg mL–1 of heparin, 10 mg mL–1 of theophylline, 1 mM calcium ionophore A23178 and 10 μg of heparin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…As compared with previous studies in dromedary camel using freshly collected cauda epididymal spermatozoa, the cleavage rate recorded herein (36.28%) was similar to 37.68% (Badr and Abdel-Malak, 2010), higher than 15-32% (Nowshari and Wani, 2005;Moawad et al, 2011) and lower than 43-60% (Wani, 2009). Using the freshly collected cauda epididymal spermatozoa, the morula production rate reported herein (19.76%) was more or less similar to the reported results after IVF of dromedary (21.32%, Badr and Abdel-Malak, 2010;20.0%, Fathi et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…As compared with previous studies in dromedary camel using freshly collected cauda epididymal spermatozoa, the cleavage rate recorded herein (36.28%) was similar to 37.68% (Badr and Abdel-Malak, 2010), higher than 15-32% (Nowshari and Wani, 2005;Moawad et al, 2011) and lower than 43-60% (Wani, 2009). Using the freshly collected cauda epididymal spermatozoa, the morula production rate reported herein (19.76%) was more or less similar to the reported results after IVF of dromedary (21.32%, Badr and Abdel-Malak, 2010;20.0%, Fathi et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…For preparing the Tris lactose amylase extender supplemented with caffeine (TL_AC), a (4 mM) concentration of caffeine [Sigma-Aldrich, China, Pcode: 1001176428] was used in this experiment. This concentration was based on a preliminary study along with concentrations cited in [25] , [26] .…”
Section: Methodsmentioning
confidence: 99%
“…Caffeine in camel semen processing for IVM and IVF in vitro trials, showed improvement in semen characteristics during processing [24] , [25] , [26] . Furthermore, the addition of caffeine improved motility of individual camel spermatozoon and decreased acrosomal damage in semen used for female in vivo trials [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the reproductive efficiency in camelids is low, partly due to the late onset of puberty, early embryonic mortality, seasonality and the length of the gestation period (13 months). Although recent reproductive technologies such as IVF [ 34 , 35 ] and somatic cell nuclear transfer (SCNT) [ 36 ] have been successfully applied to camelids and the birth of live offspring following these technologies has been reported [ 36 , 37 ], in vitro embryo production (IVP) is still not well-developed in this species compared with other domestic species. One of the main factors contributing to this situation is the limited availability of oocytes due to the shortage of abattoirs slaughtering female camels as well as the lack of a standardized protocol for in vitro maturation (IVM) and IVF of dromedary camel oocytes.…”
Section: Introductionmentioning
confidence: 99%